Schizophrenia and functioning: correlation between functioning assessment short test and years of disorder - Osorio-Martínez, Miriam L. (2017)
Introduction: Schizophrenia is associated to progressive deterioration of the person’s skills in several areas of life. However this fact has not been studied in our population. Objective: To identify the effect of schizophrenia on functioning according to time. Design: Analytical correlational, cross-sectional observational study. Location: Hospital Hermilio Valdizan, Lima, Peru. Participants: Outpatient subjects diagnosed with schizophrenia. Interventions. Interview and application of scales to 136 patients in 4 groups of 34 according to time of sickness. The analysis was performed with t-student tests, Kruskal-Wallis, Mann Whitney U test and Spearman correlation, with a 95% confidence interval, p <0.05. Main outcome measures: Measurement of functioning with the Short Scale Performance Review (FAST) and measurement of psychotic symptoms with the Brief Psychiatric symptoms Rating Scale (BPRS) were done. The FAST score is inversely proportional to functioning. Results: 57% of patients were male, 47.9% in the 21-30 age range. The FAST score for the group with less than 1 year of disease was 50.2 + 9.3, for 1-5 years 57.1 + 10.6, 6-10 years 59.0 + 9.7, and more than 10 years of illness 60.2 + 10.1. There was a significant difference (p <0.005) for in functioning between the group with less than one year of disease versus the other groups. Conclusions: Patients with less than one year of disease showed better functioning. Decreased functioning was observed after the first year of diagnosis, without distinction between groups. There is a need for early rehabilitation strategies starting in schizophrenia.